Efficiency of open bite treatment with fixed palatal crib in early and late mixed dentition - Eto, Henrique Campos (2024)
Objective: The objective of this study was to evaluate the influence of age, severity of open bite and persistent sucking habits on the open bite correction. Secondary, to compare dentoskeletal changes, treatment length, and efficiency produced by fixed palatal cribs in patients with anterior open bites at the early and late mixed dentitions. Methods: The sample was composed of patients aged from 6 to 11 years with anterior open bite. All patients were treated with fixed palatal cribs. Digital models were obtained at pretreatment (T1), after 3 months of treatment (T2), and after 6 months of treatment (T3). Lateral head films were obtained at pretreatment (T1) and after the open bite correction or until the completion of 12 months of treatment (T2). A multiple linear regressions analysis was performed in the total sample to evaluate the influence of initial age, initial overbite, and persistent deleterious oral habits on the changes in arch width, arch length, overjet, and overbite (p<0.05). Sex distribution and treatment success rates were compared between groups using the Fisher exact test. Intergroup comparisons regarding initial age, average treatment time, and dentoskeletal changes were performed with t or Mann-Whitney U tests. For this test, 31 patients were divided in two groups. Results: Initial age showed a positive influence in intercanine width increase and negative influence in arch length. There was a positive correlation between initial age and overbite changes. In the presence of persistent sucking habits at pre-treatment, the overbite change was 1.25 mm greater during therapy compared to those patients with absent sucking habits at pre-treatment. The maxillary and mandibular incisors showed a similar lingual inclination during treatment. Both groups showed similar increases in the overbite. Conclusions: The greater severity of the initial overbite, the presence of persistent sucking habits at pretreatment, and the younger the patient influenced positively in the efficiency of the open bite correction in the mixed dentition. The overbite increase produced by fixed palatal crib therapy was similar in the early and late mixed dentitions.